A Reference Chronology of Events Significant in the Development of Accountancy in the United States. - Chatfield, Michael; Dominiak, Gere (The Accounting Review, 1977)
Abstract Reviews the book 'A Reference Chronology of Events Significant to the Development of Accountancy in the United States,' by C.L. Knight, G.J. Previts and T.A. Ratcliffe.